2021
DOI: 10.1016/j.clinimag.2021.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification in COVID-19 patients: an imaging biomarker for adverse clinical outcomes

Abstract: Background: Recent studies have demonstrated a complex interplay between comorbid cardiovascular disease, COVID-19 pathophysiology, and poor clinical outcomes. Coronary artery calcification (CAC) may therefore aid in risk stratification of COVID-19 patients. Methods: Non-contrast chest CT studies on 180 COVID-19 patients ≥ age 21 admitted from March 1, 2020 to April 27, 2020 were retrospectively reviewed by two radiologists to determine CAC scores. Following feature selection, multivariable logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 35 publications
4
32
2
Order By: Relevance
“…However, it is relevant to underline that all consecutive patients by each participating center were enrolled. Moreover, our study population's clinical, laboratory, and outcome features were consistent with those previously reported in the literature for COVID-19 [17][18][19][20].…”
Section: Discussionsupporting
confidence: 87%
“…However, it is relevant to underline that all consecutive patients by each participating center were enrolled. Moreover, our study population's clinical, laboratory, and outcome features were consistent with those previously reported in the literature for COVID-19 [17][18][19][20].…”
Section: Discussionsupporting
confidence: 87%
“…CACS can be easily measured from chest CT performed for pneumonia assessment [ 7 , 9 , 16 18 ], and CACS has been demonstrated to be a strong independent predictor of future cardiovascular events [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, even though coronary artery calcium was detected in half (50.7%) of the patients in the Dillinger study [15], the overall plaque burden was relatively low with a median CACS of 8 (IQR: 0-116) [15]. Recently, Gupta et al [16] conducted a similar study on 108 hospitalized patients with COVID-19 and showed that CACS were associated with the primary outcome of intubation/death, and the secondary outcome of elevated D-dimer. Similar to the study by Dillinger [15], they found both the presence of calcified plaque and extent of plaque were associated with worst outcomes even after adjusting for a broad set of demographic, clinical and laboratory covariates.…”
mentioning
confidence: 95%
“…In this issue of Atherosclerosis, Scoccia et al present an interesting study on the prognostic role of coronary artery calcium scores (CACS) in COVID-19 [1]. They used a large unselected population of patients hospitalized in 16 Italian hospitals for severe COVID-19. CACS were computed from clinically indicated non-gated chest computed tomography (CT) scans and patients were divided into 3 categories of coronary artery disease (CAD): no CAD (CACS = 0), prior CAD (history of previous surgical or percutaneous coronary revascularization) or subclinical CAD (further classified based on CACS as mild: ≤100; moderate: 100-400; and severe: >400).…”
mentioning
confidence: 99%
See 1 more Smart Citation